Comprehensive analysis of miRNA–mRNA–lncRNA networks in severe asthma. (14th November 2018) - Chen, Yi; Mao, Zheng-Dao; Shi, Yu-Jia; Qian, Yan; Liu, Zhi-Guang; Yin, Xiao-Wei; Zhang, Qian
Aim: This study aimed to explore the molecular mechanism of severe asthma.Materials & methods: The shared and divergent differentially expressed mRNAs (DEmRNAs), miRNAs (DEmiRNAs) and lncRNAs (DElncRNAs) in asthma and severe asthma were identified by RNA-sequencing. Severe asthma-specific and shared DEmiRNA–DEmRNA–DElncRNA interaction networks were performed.Results: Compared with normal control, 1328 DEmRNAs, 608 DElncRNAs and 63 DEmiRNAs were identified in severe asthma. Compared with asthma, 95 DEmRNAs, 143 DElncRNAs and 96 DEmiRNAs were identified in severe asthma. MiR-133a-3p- EFHD2 / CNN2 -AC144831.1 interactions and miR-3613-3p- CD44 / BCL11B -LINC00158/CTA-217C2.1/AC010976.2/RP11-641A6.2 interactions were speculated to involve with the development of severe asthma. The results of GSE69683 validation were generally consistent with our RNA-sequencing results.Conclusion: This study provides clues for understanding the mechanism of severe asthma.